Archibald Henry Sayce (1845–1933) and the Transition from 19th-Century Comparative Philology to 20th-Century General Linguistics - Subbiondo Joseph L.; Kilarski Marcin (Studia Anglica Posnaniensia)
In language study in the West, the nineteenth century was dominated by comparative philology, and the past century by general linguistics. In the last quarter of the nineteenth century, linguists introduced ideas inconsistent with traditional comparative philology that foreshadowed general linguistics. While Ferdinand de Saussure (1857–1913) is recognized as a leading founder of general linguistics, other linguists also moved the discipline in this direction. We focus on Archibald Henry Sayce’s (1845–1933) Principles of Comparative Philology (1893) because it anticipated general linguistics, and because the book and its author have been overlooked despite their relevance to the history of linguistics. However, as the author of several works on the languages, literatures, and religions of the Ancient Near East, Sayce was regarded as one of the most erudite scholars of his time. As an example of Sayce’s innovative contribution, we examine his theoretical and methodological principles, including the need for inductive generalizations based on large samples of data, the value of lesser-known languages as a window onto fundamental principles of language, and the status of linguistics vis-à-vis emerging fields of related study. Sayce’s treatment of examples from non-Indo-European languages reflects a tension between comparative philology as it was practiced in the late nineteenth century and twentieth-century comparative and typological linguistics. On the one hand, the principles mentioned above are indicative of the uniformitarian principle, the emphasis on inductive generalizations in American structuralism, and the avoidance of various types of bias in modern typology. On the other hand, his reinterpretation of examples from the languages of North America, Southern Africa, and Tasmania as evidence of the lack of abstract and generic terms not only violated his methodological assumptions but was also consistent with the common nineteenth-century practice of treating words as an index of civilizational development.